FILM DOKUMENTER WISATA ALAM KOTA SUNGAI PENUH - SOFYAN UTAMA, Dr. Budiwirman, M.Pd., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Natural tourist attraction in Sungai Penuh City are Bulit Khayangan located in Renah Kayu Embun Village and Puti Senang Flower Garden located in Talang Lindung Village. The background of this documentary film is due to the lack of socialization and information to the public in preserving the tourist attractions. The documentary film aims to enable the public to know the tourist attractions located in Sungai Penuh City in order to be improved in the future. This documentary film is also supported by several other media that help the mainstream media to introduce the subject to audience as the target, such as movie posters, CD covers and CD labels, T-shirts, Stickers, flyers, X-banners.The methodology used is the 5W + 1H approach which is used as the basic concept of problem solving : what, who, when, where, why and how. The purpose of this 5W + 1H analysis is to give an overview of the results of the analysis used as the basis of objective preparation and strategy in design. Therefore, all aspects that are summarized in natural tourist attractions in Sungai Penuh City are able to be packed into documentary film media, so that the documentary of natural tourist attractions in Sungai Penuh City can be an effective and communicative media.Keywords: Documentary Film, Natural Tourist Attraction in Sungai Penuh City1Mahasiswa penulis